DEVELOPMENT OF POWERPOINT-BASED INTERACTIVE LEARNING MEDIA ON CLASS VIII EXCRETORY SYSTEM MATERIAL SMP (Program Studi Pendidikan IPA FIP Universitas Hasyim Asy'ari, 2023)
Learning media had an important role in the learning process. The selection of appropriate learning media can increased students motivation and understanding in the teaching and learning process. One of the media that often used was PowerPoint, which can presented text, images, and animated videos. However, in one SMPN Riau, still used whiteboard as a learning. The aims of this research was to produced PowerPoint-based interactive learning media on the excretory system material that was feasible to used. This research followed the ADDIE development procedure through analysis, design, development, implementation, and evaluation. The validator declared the results of this study were very valid with an average score of 3.72. The practical test results obtained from the implementation of the media usage sheet and questionnaire responses of students achieved an average score of 92.16%, indicating very practical criteria. The effectiveness of the media was then evaluated based on the results of the post-test, which showed an average value of 87.5, which indicated very effective criteria. Thus the PowerPoint-based interactive learning media that has been developed is deemed fit to be used as a learning media.